KOMPETENSI GURU DALAM PEMBELAJARAN MELALUI SUPERVISI EDUKATIF KOLABORATIF SECARA PERIODIK - Eka Herwira; Khamsir Khamsir (Cerdas Proklamator, 2022)
The teacher is one of the important components in the learning process, the teacher plays a role in creating a process of interaction in all directions between students, teachers and learning resources so that learning objectives are realized. Although the current learning system is no longer a teacher center, a teacher still plays an important role in guiding students. To improve the performance and insight of teachers in learning at SD Negeri 016/XI Talang Lindung, schools carry out action research related to the problems above. Due to the limitations of the researcher, this research is only focused on educative supervision, so the title of the action research is "Improving Teacher Performance in Classroom Learning Through Periodic Collaborative Educational Supervision". Based on the background of the problem above, the general problem formulation in this action research is: Can collaborative educational supervision periodically improve teacher performance in classroom learning? The subjects in this study were the teachers of SDN 016/XI Talang Lindung Sungai Bungkal District, Sungai Penuh City, where the researcher was assigned to be the principal of the 2019/2020 school year. The action is carried out in 2 cycles. The research time is from August to October 2019 in the 2019/2020 school year. In the implementation of the action, the design is carried out in 2 cycles which include; (1) planning, (2) action, (3) observation, (4) reflection. During the research, the researcher collected initial data, developed a supervision program, carried out supervision, analyzed, and followed up. In data collection, the technique used is to use observation and questionnaires. In this action research, it turned out that almost all of the 6 teachers were able to carry out learning well. This is evident from the results of supervision. Based on the improvement in teacher performance, both lesson plans, implementation of learning, assessment of learning outcomes, and implementation of follow-up on student assessment results, it turns out that it affects student test results in 2019. Thus, the hypothesis proposed above can be accepted